Highly Sensitive Measurement of Inositol 1, 4, 5‐Trisphosphate by Using a New Fluorescent Ligand and Ligand Binding Domain Combination. (30th June 2016) - Oura, Tai; Murata, Kaori; Morita, Takao; Nezu, Akihiro; Arisawa, Mitsuhiro; Shuto, Satoshi; Tanimura, Akihiko
Abstract: Based on the results of our previous adenophostin A structure–activity relationship studies, two fluorescent inositol 1, 4, 5‐trisphosphate (IP3 ) receptor ligands, fluorescent adenophostin A (FADA) and fluorescent low‐affinity ligand (FLL), were designed. Binding of the fluorescent ligands to the fluorescent IP3 sensor in protein‐expressing cells caused FRET. This principle was extended to a cell‐free assay system by using the fluorescent IP3 sensor bound to agarose beads. The effect of FLL on the FRET signal was reduced by subsequent addition of IP3 . The IC50 values of IP3 on the FRET signals were 139.7 and 352.1 nm for 30 and 100 nm FLL, respectively. This method allowed quantitative measurement of IP3 concentrations below 10 nm and was applied to measure cytosolic IP3 concentrations in COS‐7 cells and to examine the potency of synthesized adenophostin A analogues. Abstract : The binding of fluorescent ligand (FL) to a sensor consisting of fluorescent protein (CFP) and the ligand binding domain of the IP3 R (LBD) causes FRET. Excitation of CFP leads to transfer of the excitation energy to FL. IP3 competes with FL for binding to the LBD, thereby resulting in a decrease in the FRET signal.